SYNTHESIS AND PROPERTIES OF BIMETALLIC PHOSPHIDE Ni-Cu-P ELECTROCATALYST FOR WATER ELECTROLYSIS (Scientific journal of the Fergana State University, 2025)
Ni-Cu-P synthesis was carried out by a one-step hydrothermal method. The structural properties of the sample were studied using scanning electron microscopy (SEM), energy-dispersive spectroscopy.